VARIABEL-VARIABEL YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA INDUSTRI PERAK DI KECAMATAN SUKAWATI GIANYAR - Dewi, Anak Agung Diah Pradnya; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 11 (2021): VOL 10 NO 11, NOVEMBER 2021 [4406 - 4562], 2021)
The existence of an industry in an area will certainly affect socio-economic conditions by absorbing labor in the surrounding community. The objectives of this study were: 1) to analyze the effect of capital, education, and wages simultaneously on the absorption of labor in the silver industry 2) to analyze the effect of capital, education and wages simultaneously on the absorption of labor in the silver industry. This research was conducted in Sukawati which has 113 business units of silver craftsmen. The object of this research silver industry owners in Sukawati District. The sample in this study amounted to 53 respondents. This study uses Multiple Linear Regression, Classical Assumption Test, F Test and t Test. Based on the results obtained, it shows that 1) capital, education, and wages simultaneously have a significant effect on labor absorption, 2) capital, education, and wages partially have a positive and significant effect on labor absorption in the silver industry in Sukawati Gianyar District. Keywords : silver industry, capital, education, wages, labor